2017
DOI: 10.1177/0309364616683980
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous stiffness and hysteresis of dynamic elastic response prosthetic feet

Abstract: Mechanical testing is a reproducible method that can be used to provide objective evidence about dynamic elastic response prosthetic foot performance and aid in the prescription process. Clinical relevance The quantitative stiffness and hysteresis data from this study can be used by prosthetists to aid the prescription process and make it more objective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 30 publications
3
35
0
Order By: Relevance
“…20,21 Stiffness and ESR characteristics, including hysteresis effects, are important properties that have been tested for different dorsi/plantar-flexed positions to simulate prosthetic foot behavior in normal gait. [22][23][24][25] It has also been shown that mechanical functions of prosthetic feet can be altered by footwear. 22,26 Another important parameter, which can be emulated using mechanical testing, is the roll-over shape and therefore the course of the center of pressure (COP) beneath the foot during loading.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Stiffness and ESR characteristics, including hysteresis effects, are important properties that have been tested for different dorsi/plantar-flexed positions to simulate prosthetic foot behavior in normal gait. [22][23][24][25] It has also been shown that mechanical functions of prosthetic feet can be altered by footwear. 22,26 Another important parameter, which can be emulated using mechanical testing, is the roll-over shape and therefore the course of the center of pressure (COP) beneath the foot during loading.…”
Section: Introductionmentioning
confidence: 99%
“…Both stiffness 1317 and energy storage and return 1820 properties have been shown to have a significant influence on amputee gait. As a result, a number of studies have attempted to quantify prosthetic foot stiffness 2125 or energy storage properties. 2128 These studies often make measurements for a few conditions: loading either the prosthetic heel to simulate heel strike or the forefoot keel to simulate toe off.…”
Section: Introductionmentioning
confidence: 99%
“… 1 While the exact mechanics of ESR prosthetic feet are complex, a common, simplified model consists of a solid foot attached to the shank via a rotational spring, articulating around an estimated ankle axis. Damping is present to varying degrees, but elasticity (stiffness) dominates the mechanics; for example, in ESR feet without a shock absorber (i.e., no damping), only 5–15% of the energy stored is lost [ 30 ]. …”
mentioning
confidence: 99%